THE PRINCIPAL'S LEADERSHIP STYLE IN IMPROVING THE SPIRITUAL AND INTELLECTUALITY OF STUDENTS AT AN-NAHDLIYAH PANGURAGAN KULON VOCATIONAL SCHOOL, CIREBON - Muhammad Akrom (Media Inovasi Pendidikan dan Publikasi, 2024)
Leadership as part of the management function is very important to achieve organizational goals. A leader is essentially someone who can influence the behavior of other people in their work by using power. The principal is the leader of the educational unit. The success of a school principal's leadership is based on one theory or model of leadership. In educational institutions, the principal holds power. The principal in carrying out his duties influences his subordinates through an approach or style that can have direct contact with students in upgrading their spiritual and intellectual intelligence. Therefore, this research is motivated by how the school principal's leadership style improves these two aspects of intelligence in students at An-Nahdliyah Panguragan Vocational School, Cirebon, so that students can apply and implement the instructions of the school principal and his subordinates. The writing method in this research is classified as qualitative research. Determining the selected informants using purposive techniques. Data collection was carried out using in-depth interview techniques, observation, and documentary studies. The data analysis process includes 3 things, namely data reduction, data presentation, and conclusion. The results of this research show that the principle of An-Nahdliyah Vocational School uses a charismatic style in improving the spirituality of students, while in improving students' intellectual development he uses an autocratic style. The charismatic style encourages students to be more moral and ethical in the social and religious spirit (religious) while the autocratic style makes students active in discipline, interactive in knowledge, and able to compete in work.